A Review on Novel Method of Milk Processing (International Journal of Innovative Research in Engineering & Management, 2023)
This chapter examines a variety of milk processing methods that are either new or emerging. Thermal therapies have traditionally been used in the dairy  sector since they are effective in inactivating bacteria as  well as enzymes. Several of these heat treatments,  however, cause significant chemical changes in the food,  leading to variations not only in the sensory aspects of the  meal, but also in its nutritional content. Due to these  constraints, the dairy sector is looking for new ways to  enhance existing products and create new ones which are  high-quality as well as consistent. The bulk of these cutting-edge technologies aren't brand new; they've been  tried and proven in the food industry for decades. Their  resurgence has lately been fueled by technological and  scientific advancements, as well as consumer desires for  minimally processed meals. The authors have tried to  gather the most researched technologies that are  alternatives to traditional thermal treatments in this  chapter. The following subjects are covered: general  issues, impacts on microbes and enzymes, as well as  chemical and sensory changes. Despite the large number  of studies that have been completed, additional study is  required to confirm the efficacy of these technologies and,  as a result, to find serious alternatives to conventional  therapies.
Keywords: Enzymes; Microwave; Microbes; Milk Bacteria